Does demand volatility lower growth and raise inflation? : evidence from the Caribbean - Kandil, Magda ([Caribbean Centre for Money & Finance] [St. Augustine], 2007)
Seeks to shed some light on structural rigidities governing the relation between demand variability and economic performance. Traces the nature of cyclical fluctuations on the macro-economy across a sample of 15 Caribbean countries.